2017
DOI: 10.1186/s13256-017-1201-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute corneal hydrops during pregnancy with spontaneous resolution after corneal cross-linking for keratoconus: a case report

Abstract: BackgroundKeratoconus may progress to acute corneal hydrops even after cross-linking. In some cases, keratoconus progresses during pregnancy. In this report, we present a case of a patient with increased anterior stromal resistance after cross-linking that would favor nonprogression of keratoconus during pregnancy.Case presentationWe report that cross-linking is likely to have had a protective effect in a white pregnant patient with acute corneal hydrops who showed rapid improvement, as documented by corneal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
2
15
0
2
Order By: Relevance
“…Certain eye diseases have been associated with pregnancy, such as corneal ectatic diseases and glaucoma. 13 Fluctuations of sex hormones during pregnancy may influence the intraocular pressure (IOP), central corneal thickness (CCT), and corneal biomechanical properties of pregnant women. 47 Increase in CCT and decrease trend in IOP are known to occur along the pregnancy period, especially in the second and third trimesters when compared to the non-pregnant and the post-partum period.…”
Section: Introductionmentioning
confidence: 99%
“…Certain eye diseases have been associated with pregnancy, such as corneal ectatic diseases and glaucoma. 13 Fluctuations of sex hormones during pregnancy may influence the intraocular pressure (IOP), central corneal thickness (CCT), and corneal biomechanical properties of pregnant women. 47 Increase in CCT and decrease trend in IOP are known to occur along the pregnancy period, especially in the second and third trimesters when compared to the non-pregnant and the post-partum period.…”
Section: Introductionmentioning
confidence: 99%
“…Methods like pneumatic descemetopexy have been shown to fasten the speed of recovery 7–9. Two case reports where acute CH developed in a post-CXL cornea showed a complete resolution time of 7–8 days 2 10. The same was 21 days in the above described clinical case.…”
Section: Discussionmentioning
confidence: 69%
“…Stock and al. (6) reported a case of a 26-year-old woman who developed acute hydrops 7 months after uneventful standard CXL in one eye during the fifth month of pregnancy. Hydrops resolved, and the authors postulated that CXL led to the greater resistance of aqueous passage through the cornea, which accelerated the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of cross-linking (CXL) has changed the course of KC progression with a high rate of success in halting the disease (3) . Yet, three reports (4)(5)(6) revealed that KC can progress to corneal hydrops months to years after CXL. To our knowledge, this is the first described case of acute hydrops followed by corneal perforation five years after CXL.…”
Section: Introductionmentioning
confidence: 99%